Exploring Community Perceptions of Halal Slaughtering: Its Impact on Family and Social Obligations in Ampara District, Sri Lanka - Iqbal Saujan; M.H.M.Sifkan; S.I. Nimsith; S.M.M. Nafees (QURU’: Journal of Family Law and Culture, 2025)
Islam serves as a comprehensive guide for human beings, governing their daily affairs, including earthly life and the hereafter. Islamic jurisprudence categorises all human conduct into permissible (halal) and forbidden (haram). Islam emphasises the proper preparation of halal meat for consumption. This study aims to explore perceptions of halal slaughtering among butchers in the Ampara district of Sri Lanka's Eastern province. In this qualitative study, researchers used a descriptive approach. Data were collected through questionnaires and literature review to construct a framework of Halal Slaughtering (Dhabihah). The study used Purposive Sampling Method (PSM) to select 100 butchers, with 88 usable questionnaires returned (Response rate 88%). Descriptive statistical analysis was conducted using SPSS (Version 24). Findings indicate participants have a comprehensive understanding of halal slaughtering practices as prescribed in Islamic law. However, the study identifies areas of deficiency in perceptions, particularly regarding animals not witnessing slaughter (X̄ = 3.00), facing the Qiblah (X̄=3.01), and severing trachea, larynx, and associated structures in a single operation (X̄ = 3.09). Knife sharpening (X̄ = 4.98) and continuous slaughter of multiple animals recitation of "Bismillahi Allahu Akbar" during slaughtering cannot be ensured. To ensure strict implementation of halal slaughtering, The Halal Assessment Council (HAC) should initiate mechanisms to ensure halal slaughter and issue authenticity certificates, Al Cylon Jamiyyathul Ulama and All Mosques Federation organise awareness programmes for butchers and provide guidance, and revoke permits for proprietors not adhering to halal regulations. Furthermore, the researchers posit that the study's outcomes will establish a foundation for future research endeavours and prompt policymakers to consider regulating halal slaughtering processes.